Reversible crystalline-amorphous phase transformation in Si nanosheets with lithi-/delithiation. (26th May 2017) - Park, Jeong Min; Cho, Jae-Hyun; Ha, Jung Hoon; Kim, Hae-Sik; Kim, Sung-Wook; Lee, Jaejun; Chung, Kyung Yoon; Cho, Byung-Won; Choi, Heon-Jin
Abstract: Silicon (Si) has a large theoretical capacity of 4200 mAhg −1 and has great potential as a high-performance anode material for Li ion batteries (LIBs). Meanwhile, nanostructures can exploit the potential of Si and, accordingly, many zero-dimensional (0D) and one-dimensional (1D) Si nanostructures have been studied. Herein, we report on two-dimensional (2D) Si nanostructures, Si nanosheets (SiNSs), as anodes for LIBs. These 2D Si nanostructures, with a thickness as low 5 nm and widths of several micrometers, show reversible crystalline–amorphous phase transformations with the lithi-/delithiation by the dimensionality of morphology and large surface area. The reversible crystalline–amorphous phase transformation provides a structural stability of Li + insertions and makes SiNSs promising candidates for reliable high-performance LIBs anode materials.